Effectiveness and safety of chest pain assessment to prevent emergency admissions: ESCAPE cluster randomised trial. Issue 7621 (18th September 2007) - Goodacre, Steve; Cross, Elizabeth; Lewis, Cath; Nicholl, Jon; Capewell, Simon
Abstract : Objective To determine whether introducing chest pain unit care reduces emergency admissions without increasing reattendances and admissions over the next 30 days. Design Cluster randomised before and after intervention trial. Setting 14 diverse acute hospitals in the United Kingdom. Participants Patients attending the emergency department with acute chest pain during the year before and the year after the intervention started. Intervention Establishment of chest pain unit care compared with continuation of routine care. Main outcome measures Proportion of chest pain attendances resulting in admission; reattendances and admissions over the next 30 days; daily emergency medical admissions (all causes); and proportion of emergency department attendances with chest pain. Results The introduction of chest pain unit care was associated with weak evidence of an increase in emergency department attendances with chest pain (16% v 3.5%; P=0.08); no change in the proportion of chest pain attendances resulting in admission (odds ratio 0.998, 95% confidence interval 0.940 to 1.059; P=0.945); small increases in the proportion reattending (odds ratio 1.10, 1.00 to 1.21; P=0.036) or being admitted (1.30, 0.97 to 1.74; P=0.083) over the next 30 days; and evidence of increased daily medical admissions (1.7 per day, 95% confidence interval 0.8 to 2.5; P<0.001). However, this last finding was highly sensitive to changes in the method used to handle missing data. Conclusion The introduction of chest pain unit care did not reduce the proportion of patients with chest pain admitted and may have been associated with increased emergency department attendances with chest pain. Trial registration Current Controlled Trials ISRCTN55318418 .